Pengaruh Konsentrasi dan Waktu Perendaman Ampas Tebu terhadap Kadar Akrilamida pada Minyak Goreng Bekas - Gatut Ari Wardani; Widdy Erlinasari; Lilis Tuslinah (Jurnal Farmasi Indonesia, 2022)
Hydrolyzed cooking oil will form glycerol and free fatty acids, so that when heated glycerol will form acrolein, one of the compounds forming acrylamide. Bagasse contains cellulose which can bind acrylamide. The purpose of this study was to determine the effect of adding pulp and the effect of soaking time on acrylamide levels. Analysis was performed using High-Performance Liquid Chromatography, column Agilent TC-C18 mobile phase 0.1% phosphoric acid and methanol in a ratio of 95:5; flow rate 1 mL/min; the sample volume injected was 20µL. Acrylamide in oil was identified at a retention time of 4,939 minutes, theoretical plate 39,029, HETP 0.00064, and capacity factor 2.265 This study meets the method validation parameters such as linearity with the results of y = 259.37x + 103.39 and a correlation coefficient of 0.9993, precision with % RSD < 2%, detection limit 0.46 ppm, quantification limit 1.396 ppm, accuracy with % recovery 94 .55 - 100.04. The results of FTIR, bagasse can bind the C=O and C-H groups of one of the acrylamide groups. The adsorption kinetics model used was the Ho model with linearity of 0.9752. Sugarcane bagasse concentration of 5% and soaking time of 24 hours affected the decrease in acrylamide levels in used cooking oil. Soaking used cooking oil samples with 5% bagasse for 24 hours can reduce acrylamide levels by 65%.